Implementation of Failover Recursive Gateway and Load Balancing PCC Method on Internet Networks at Universitas Semarang - Surono, Surono; Setiarso, Galih; Hadi, Soiful (Politeknik Negeri Lhokseumawe, 2025)
This study implements and analyzes failover recursive gateway and load balancing using the Per Connection Classifier (PCC) method on the internet network at Universitas Semarang to enhance the reliability and efficiency of bandwidth distribution. The methodology involves using Wireshark for network data testing and analysis. The results demonstrate three main achievements: (1) bandwidth from both ISPs is evenly distributed, (2) the failover system functions optimally by automatically switching to the active link if one ISP fails, and (3) the method effectively balances bandwidth and manages connection disruptions. Before implementation, ping tests to www.google.com showed an average response time of 62 ms, with balanced upload/download speeds of 100 Mbps. After implementation, the ping response remained stable at 62 ms, while upload speeds increased to 158 Mbps and download speeds to 144 Mbps. This study proves that failover recursive gateway and PCC-based load balancing improve network stability and efficiency, providing a reliable solution for bandwidth management and connection continuity at Universitas Semarang.